Ecopack: the recycled auto-packing trash can / Muhammad Seth Kamarulzaman ... [et al.] - Kamarulzaman, Muhammad Seth; Zarak Yunus Khan, Muhammad Mikhail Khan; Ismadi, IsmaZikry Ridhuan; Haikal Juwari, Nur Syafiq (2024)
EcoPack: The Recycled Auto-Packing Trash Can address the growing environmental concern of waste management by introducing an innovative solution that optimises trash disposal. The increasing volume of waste, coupled with inefficient trash packing, exacerbates landfill overflows and environmental pollution. EcoPack aims to reduce waste volume and enhance recycling efficiency through an automated, eco-friendly trash can. Utilising a mechanism that compresses and packs trash into recyclable materials, EcoPack integrates sensors and smart technology to detect and sort different types of waste. The methodology involves the development of a prototype equipped with solar-powered compactors, IoT-enabled sensors, and an easy-to-use interface for consumers. Initial tests demonstrate significant reductions in waste volume and improvements in recycling rates. In short, EcoPack presents a sustainable solution to modern waste management challenges, promoting environmental conservation and resource efficiency. The project aims to revolutionise household waste disposal and contribute to broader efforts in reducing the global environmental footprint.